IS CULTURAL BACKGROUND MODERATING THE DESTINATION PERSONALITY AND SELF IMAGE CONGRUITY RELATIONSHIP OF BEHAVIORAL INTENTION? - Suryaningsih, Ika Barokah; Nugraha, Kristian Suhartadi Widi; Anggita, Reza May (Universitas Brawijaya, Indonesia, 2020)
Behavioral Intention is one way of keeping a destination to be sustainable. Destination Personality is one crucial factor that influences Behavioral Intention. The destination personality of a tourist attraction that is following the selfimage congruity of visitors will lead to positive behavioral intention. The subjects of this research are all visitors of Tanoker, Ledokombo. The sample in this study was 137 respondents and the method used was non-probability sampling withÂ a purposive sampling approach technique. This research analysis technique uses the Moderated Structural Equation Modeling (MSEM) approach. The results of this study indicate that destination personality, self-image congruity affect behavioral intention. Also, cultural background moderating variables play a role in strengthening the relationship of destination personality, and self-image congruity towards behavioral intention. However, the cultural background has not been proven significant in moderating the relationship between destination personality and behavioral intention.